2020
DOI: 10.1038/s41598-020-77779-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar network organization across the human menstrual cycle

Abstract: The cerebellum contains the vast majority of neurons in the brain and houses distinct functional networks that constitute at least two homotopic maps of cerebral networks. It is also a major site of sex steroid hormone action. While the functional organization of the human cerebellum has been characterized, the influence of sex steroid hormones on intrinsic cerebellar network dynamics has yet to be established. Here we investigated the extent to which endogenous fluctuations in estradiol and progesterone alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…These results suggest that the endocrine system, and specifically reproductive hormones, are a key factor in modulating "events". While this observation is in line with previous studies that have reported links between reproductive hormones and both brain activity [21,22] and functional connectivity [23,26,[34][35][36][37][38][39][40], our results extend this link to ultrafast network dynamics. Changes in network structure at this timescale have been relatively unexplored in previous studies due to their cross-sectional study design and low temporal resolution of sliding-window methods for estimating time-varying functional connectivity [41] (although, see [24]).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results suggest that the endocrine system, and specifically reproductive hormones, are a key factor in modulating "events". While this observation is in line with previous studies that have reported links between reproductive hormones and both brain activity [21,22] and functional connectivity [23,26,[34][35][36][37][38][39][40], our results extend this link to ultrafast network dynamics. Changes in network structure at this timescale have been relatively unexplored in previous studies due to their cross-sectional study design and low temporal resolution of sliding-window methods for estimating time-varying functional connectivity [41] (although, see [24]).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we built upon previous analyses of a densesampling dataset in which a single participant underwent daily MRI scans and serological sampling over the course of two full menstrual cycles [23][24][25][26]. Leveraging "edge time series" [14,15], we detected high-amplitude events in each scan session, clustering them into two large communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in a developmental cohort has shown males exhibit stronger inter-network connectivity, while females exhibit stronger intra-network connectivity (4). Extant literature also suggests hormonal modulation of functional connectivity (8,(34)(35)(36)(37). In terms of functional connectivity features that discriminate sex, two studies identified that connections within and between frontoparietal and default mode networks strongly contribute to the predictions (33,38).…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, recent work looking at hormonal fluctuations during the menstrual cycle has demonstrated that over the course of the menstrual cycle, as sex steroid hormones fluctuate, increases in network coherence are related to levels of estradiol, and when progesterone rose, network coherence declines (Pritschet et al 2020). Interestingly, when investigating the cerebellum, the dynamics were changed wherein the impacts of progesterone where larger, and those for estradiol were minimal as compared to the cortex (Fitzgerald et al 2020). While the menstrual cycle is distinct from the hormonal changes of menopause and associated hormonal milieu, this work indicates that both cortical and cerebellar functional connectivity are sensitive to circulating sex steroid hormones.…”
Section: Limitationsmentioning
confidence: 99%